Availability and Stock Outs of Paediatric Essential Medicines Across Different Levels of Care in One District - Javid Iqbal, Mir; Ishaq Geer, Mohammad; Ahamd Dar, Parvez (Indian Journal of Pharmacy Practice)
Objective: To assess the availability and stock out periods of key paediatric essential medicines across different levels of care in one district of Jammu and Kashmir state. Methods: A cross-sectional survey at public health facilities and private retail outlets in their vicinity across primary, secondary and tertiary levels of care. Results: Overall public paediatric medicine availability was low (30.46%) in comparison to the private retail outlet availability of 71.83%. In public sector, primary level of care showed highest availability of 36.27% followed by tertiary care (28.57%) whereas secondary care recorded least availability of 25%. Private retail outlets recorded highest availability at primary level (78.13%) followed by secondary level (76.25%) and tertiary level (54.78%). Among public health facilities and private retail outlets Children’s hospital recorded highest availability of 56.16% and 68.85% respectively whereas District Hospital and Primary Health Centre had lowest availability of 8.64% and 69.76% respectively. Mean stock out period was more in public sector (66.29 days) as compared to private retail outlets (34.78 days). At primary level of care mean stock out period was 88 days in public facilities as compared to 41.25 days in private retail outlets. At secondary level mean stock out period were 43.75 days in public and 34.87 days in private facilities. Tertiary level recorded mean stock out period of 22.6 days and 22.1 days at public and private facilities respectively. Conclusion: Overall availability of key essential medicines for children was low with frequent stock-outs in public hospitals which deprive the children who attend these public hospitals from adequate access to essential medicines.
Keywords: Paediatric; Essential Medicines; Availability; Stock-outs; Access; Tertiary care